The Microbiome in Rheumatic Diseases and Infection (Springer International Publishing, 2018)
This book discusses the role of the microbiome in rheumatic diseases and details its implications for patient treatment. Recently, with technological advances, there has been significant research into the microbiome. This has enabled us to more profoundly understand its role in our immune system maturation as well as the role played by microorganisms in autoimmunity and the deeply related rheumatic diseases. This book comprehensively explains the emerging microbiome research through the interrelationships of biomedical sciences, including: immunology, microbiology, bioinformatics, and, with special emphasis, the clinical aspect of rheumatology. It examines the interplay between infectious organisms and major autoimmune diseases, including rheumatoid arthritis, psoriatic arthritis, juvenile arthritis, systemic lupus erythematosus, and vasculitis, and explains how to apply that knowledge to diagnostic techniques and treatment decisions. The international team of expert authors provides insight into current therapies and future interventions specifically targeting the microbiota and explores the impact of our deeper understanding on enhancing personalized medicine. The Microbiome in Rheumatic Diseases and Infection is an essential resource for rheumatologists, pediatricians, internists, microbiologists, and critical care providers caring for children and adults with rheumatic diseases.